(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
As a unique approach to the study of automatic control systems, an algorithm for drawing up structured schemes, which is one of the forms of mathematical models of them, is presented. As an example of using the same algorithm, the structure of an automatic greenhouse temperature control system is given.